KETERAMPILAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN FISIKA PADA MATERI RANGKAIAN LISTRIK ARUS SEARAH - Erwina Oktavianty; Sudirman . (Jurnal Visi Ilmu Pendidikan, 2016)
The aim of this study is to describe the critical thinking skills students of physical education PGMIPA-U on material direct current circuits. Methods used in this study is simple descriptive. where all students PGMIPA-U ever get the material in the direction of the electric circuit asrus basic physics II participated in this research. Based on the analysis of the data found that the average critical thinking skills possessed by students of physics education PGMIPA-U on direct current electrical circuit material is 62.98%. We hope this research can be used as evidence of the earliest descriptions of the critical thinking skills that can be used by interested parties.   Key Word : Critical Thinking Skill